Q. 515.0( 1 Vote )

If <span lang="EN

Answer :

Formula: - sin2x + cos2x = 1


Given: - acosx – bsinx = c


Let find out value of


(acosx – bsinx)2 + (asinx + bcosx)2 = a2(cos2x + sin2x) + b2(cos2x + sin2x) – 2absinxcosx + 2absinxcosx


(acosx – bsinx)2 + (asinx + bcosx)2 = a2 + b2 ……(i)


we can rewrite (i) as


(asinx + bcosx)2 = a2 + b2 – (acosx – bsinx)2




Hence, Proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses